5GCHAMPION – Disruptive 5G Technologies for Roll‐Out in 2018. Issue 1 (15th February 2018) - Calvanese Strinati, Emilio; Mueck, Markus; Clemente, Antonio; Kim, Junhyeong; Noh, Gosan; Chung, Heesang; Kim, Ilgyu; Choi, Taesang; Kim, Yeongjin; Chung, Hyun Kyu; Destino, Giuseppe; Pärssinen, Aarno; et al.
Abstract : The 5GCHAMPION Europe–Korea collaborative project provides the first fully‐integrated and operational 5G prototype in 2018, in conjunction with the 2018 PyeongChang Winter Olympic Games. The corresponding technological advances comprise both an evolution and optimization of existing technological solutions and disruptive new features, which substantially outpace previous generations of technology. In this article, we focus on a subset of three disruptive technological solutions developed and experimented on by 5GCHAMPION during the 2018 PyeongChang Olympic Games: high speed communications, direct satellite‐user equipment communications, and post‐sale evolution of wireless equipment through software reconfiguration. Evaluating effectiveness and performing trials for these key 5G features permit us to learn about the actual maturity of 5G technology prototyping and the potential of new 5G services for vertical markets and end user enhanced experience two years before the launch of large‐scale 5G services.